Authorial Voice as a Censorship Avoidance Tool : Carmen Laforet Found in Translation - Sykes, Madeline (Université d'Ottawa / University of Ottawa, 2023)
This thesis explores the issue of translating works in which censoring regimes have constrained authors' voices, limiting their discussion of subversive content to a few well-placed clues. It takes as a case Carmen Laforet's "La llamada" (1954), a short story published under Spain's Franco dictatorship. At the time of its publication, a state censorship apparatus inspected all books to ensure they did not challenge the government or its Catholic morality. Laforet accordingly penned a story that superficially appears to validate Church doctrine on women's place in society, with the protagonist repenting her abandonment of the wife/mother role. However, a second and more critical interpretation emerges when the text is examined according to its historical context and the author's attitudes towards Catholicism, her country, and gender roles. The narrative voice explicitly communicating to readers is then echoing that of the regime. The author's voice parrots this discourse but simultaneously expresses dissent towards it through a series of implicatures and communicative clues. When translating a work that features such a duality of voices, the translator is responsible for ensuring that both the explicit and implicit voice are intelligible to readers with a very different cognitive environment from that of the original readers. According to my evaluation of three possible solutions to this problem - making no adjustments to preserve the narrative, compensating for readers' knowledge gaps through paratext, and inserting communicative clues to the alternative reading into the text through an interventionist translation - the third option proves to be the most effective way of conveying all voices to an average reader. My interventions in the text include straightforward explicitations on references to the era's oppressive conditions, exaggerations of the story's tremendista and traumatic elements that suggest social decay, and manipulations of the heterodiegetic narrative style to distinguish characters' subjective judgments on the protagonist from objective judgments on her.
Keywords: translation; censorship; relevance theory; voice; implicature